Adequacy of Facilities for the Implementation of the Universal Basic Education Scheme in Public Primary Schools in Ogun State, Nigeria: An Appraisal - Jayesimi, Goke (NIU Journal of Social Sciences; Vol 5 No 4 (2019): KIU Journal of Social Sciences, Vol. 5 No. 4, December 2019, 2020)
This paper examined the extent to which facilities for the full implementation of the Universal Basic Education (UBE) programme have been provided in public primary schools in Ogun State, Nigeria. The study adopted the descriptive survey design. 70 public primary schools were randomly sampled from the 7 randomly selected local government councils in the state. A self-designed instrument, the Primary School Facilities Checklist (PSFC) was used to obtain data. Data collected were analysed using frequency count, simple percentage, mean and standard deviation. Results show that some facilities were not available in many of the sampled schools and where they existed, they were either inadequate or in different stages of disrepair. This indicates that governmentâ€™s pledge to provide adequate facilities for all primary schools in the state under the UBE scheme has not been fully fulfilled. This is certain to have negative impact on the quality of primary education and the achievement of the overall objectives of the UBE scheme, especially since research has shown that school infrastructure and availability of teaching materials have significant impact on the learning outcomes of primary school pupils.  Keywords: Adequacy, Appraisal, Facilities, Implementation, Policy.